Leveraging co-crystallization to enhance therapeutic potential of anti-cancer drugs (International Journal of Pharmaceutical Sciences and Drug Research, 2026)
Pharmaceutical co-crystals incorporating a minimum of one active pharmaceutical ingredient (API) remain a significant area of interest for investigators, particularly in the field of anti-cancer drugs. Co-crystals are formed via the non-covalent association of two or more distinct drug molecules. Co-crystallization is a process that can significantly improve several physicochemical characteristics, such as bioactivity, stability, solubility, and compressibility. This review focuses on co-crystals containing anti-cancer drugs reported in the literature, examining their physicochemical properties like permeability, solubility, stability, dissolution, bioavailability, and antitumor efficacy compared to the parent compounds. Although few publications specifically address the impact of anti-cancer co-crystals on drug resistance, there is a critical need for ongoing research in this area. The rising issue of drug resistance in cancer treatment underscores the importance of leveraging co-crystal technology to develop more effective therapeutic options. This review highlights, categorizes, and compares existing studies on anti-cancer drug co-crystals and encourages future research to explore their potential in overcoming drug resistance.